Optical solitons to the Perturbed Gerdjikov-Ivanov equation with quantic nonlinearity - Ali, Karmina K. K.; Tarla, Sibel; Sulaiman, Tukur Abdulkadir; Yilmazer, Resat (Springer, 2023)
In this article, we examine the Perturbed Gerdjikov-Ivanov equation by using the Jacobi elliptic function expansion method. This results in obtaining distinct solutions including dark, bright, singular solitons, periodic waves, singular periodic waves, and Jacobi elliptic function solutions. The 2- and 3-dimensional graphs of the reported solutions are presented. The reported results may be useful in explaining the physical features of the studied equation.
Keywords: Optical soliton; Perturbed Gerdjikov-Ivanov equation; Analytical technique